2010
DOI: 10.4028/www.scientific.net/amr.139-141.2546
|View full text |Cite
|
Sign up to set email alerts
|

Study of On-Line Condition Monitoring System for Roller Based on HMM

Abstract: A kind of signal build mould and identification tool for roller of rolling mill was discussed. Basic algorithm of Hidden Markov model (HMM) theory was presented. For ψ500×2 shrewd roller of rolling mill, the paper led Short-time Fourier transform (STFT) into draw the feature of roller signal and chose Continues Gaussian Hidden Markov Model (CGHMM) to build and identify mould. The experiment installation major included: ψ500×2 shrewd rollers and roller performance test control work of rolling mill control machi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The majority of research studies concern fault detection in roller bearings, gearboxes and drivetrains, the tilting table, drivers, or the hydraulic systems [38][39][40][41][42][43]. Although there are studies for condition monitoring in rollers [44,45], no work was found dealing specifically with the coating segments, for which this paper's method is applied. The method's effectiveness was examined through nine Monte Carlo tool-replacement prediction simulations on real data.…”
Section: Methods For Assessing Rulmentioning
confidence: 99%
“…The majority of research studies concern fault detection in roller bearings, gearboxes and drivetrains, the tilting table, drivers, or the hydraulic systems [38][39][40][41][42][43]. Although there are studies for condition monitoring in rollers [44,45], no work was found dealing specifically with the coating segments, for which this paper's method is applied. The method's effectiveness was examined through nine Monte Carlo tool-replacement prediction simulations on real data.…”
Section: Methods For Assessing Rulmentioning
confidence: 99%
“…For the signal of above collection, fistly get the model feature value by the vibration phase diagram. then, train for HMM model of roller [3]. Using the detector after trainning, carry out online state identification, and verify the performance of online inspection system.…”
Section: Relationship Between Phase Point Probability Distribution Andmentioning
confidence: 99%
“…Classical signal processing technique usual strain wave, the analysis of frequency spectra and power table analysis. Since the roller working signal is very complex, its signal frequency and amplitude change at any time, belong to typical unsteady signal [3]. Classical signal processing technique, such as filtering, spectrum analysis,power spectrum analysis, etc.…”
Section: Introductionmentioning
confidence: 99%